Programación de temperaturas con sus alarmas utilizando el sensor inteligente ds1820 en comunicación one-wire con un microcontrolador. fuente de energía: 4 pilas recargables aa - Samaniego, Michael (2011)
The project that follows is the design and construction of a temperature alarm system and is based on a PIC 16F887 with a smart sensor DS1820 that uses the One-Wire communication protocol. The main objective is to improve a Temperature Control system with parameters set by the user, and to establish the respective alarms to the system. The temperature alarm system with Smart Sensor DS1820 communicates through its One-wire protocol using the microcontroller 16F887 which handles the data from the sensor to show in the LCD display. Using the program MikroC PRO FOR PIC for programming the PIC 16F887, to get the data read by the Smart Sensor DS1820, and the ranges of maximum and minimum temperature data by using the keypad 4x4, these last values are sent to microcontroller to determine if the system is stable or if you need set off the alarms.